Penerapan Teknologi Nanokomposit Pada Kemasan Pangan - Lestari, Roswita Puji; Fulazzaky, Mohamad Ali; Jumiono, Aji (Jurnal Ilmiah Pangan Halal, 2023)
Nanotechnology is the manipulation and use of materials and structures on the nanometer scale, roughly between 1 and 100 nm. Nanotechnology has invaded the agri-food industry, with many applications. Nanocomposite is one of the development technologies of Nanotechnology. Nanocomposite packaging is a polymer in which certain types of nano materials have been inserted, such as nano composite clay, nano silica particles (SiO2), carbon nanotubes, graphene, starch nanocrystals, cellulose-based nanofiber or nanowhiskers, chitin chitosan nanoparticles and other inorganics. This paper reviews the main applications of nanocomposites in the field of food packaging. The writing method used in writing this article review is a comparative writing method by collecting various sources obtained from several research journals from 2014 - 2021. From the results of this study, it was found that nanocomposites have very broad potential for their use as food packaging. Such as increasing antimicrobial ability, extending shelf life, maintaining color and sensory quality, as well as other benefits. However, it is necessary to carry out further identification regarding the nature of the interactions between nanoparticles and their effects on the food packaging application process.